Gendered agency in transcultural Hinduism and Buddhism: nuns, gurus and priestesses - Hüsken, Ute; Wittich, Agi; Spina, Nanette R. (Routledge, 2024)
Introduction / Ute Hüsken, Agi Wittich, Nanette Spina -- 1. From Matriarch to Divine Mother: Caste, Gender, and Deification in Hagiographies of Satīmā / Arkamitra Ghatak -- 2. Biographies of Enhanced Agency and Self-Made Gurus: From Housewives into Founders of Guru-Bhakti Communities / Michal Erlich -- 3. Women's Ritual Expression and Religious Agency: Om Shakti Communicating Innovation in Contemporary Hinduism / Nanette R. Spina -- 4. Forgotten priestesses: a 'witch,' a queen and a ritual stew / Tara Sheemar Malhan -- 5. Women Sharing Bhakti, Women Singing Devotion: Friends, Teachers, and Leaders in the Hindu Diaspora / Vasudha Narayanan -- 6. Reinventing Selves: Religiosity and Female Agency in the Siri Tradition of Tulunad in India / Pauline Schuster-Löhlau and Yogitha Shetty -- 7. Yoga's Red Tent: Menstrual-Oriented Iyengar Yoga Practices / Agi Wittich -- 8. Womanhood and female agency in Bengali Vaishnava Sahajiya Tradition / Amnuaypond Kidpromma -- 9. Encountering in a New Phase: Monastic Education for Buddhist Nuns in Sri Lanka / Gihani De Silva -- 10. Against Marginality, Inequality, and Dependency: Remarkable Buddhist Nuns in Sikkim / Marlene Erschbamer -- 11. Global South Coalition for Dignified Menstruation / Interview of Radha Paudel, conducted by Ute Hüsken -- 12. The Changing Attitudes towards Female Priesthood in Hinduism: Insights from Pune, Southern India / Interview of Dr. Aaryaa Joshi by Dr. Agi Wittich -- 13. Beyond Boundaries: A Modern Buddhist Nun's Journey Towards Enlightenment / Interview with Ayyā Phalañāṇī by Agi Wittich -- 14 Luminous Insight: An Interview with Ayyā Tathālokā from Dhammadharini Monastery (USA) / An Interview with Ayyā Tathālokā conducted by Nanette Spina.
Keywords: Aufsatzsammlung; Autorität; Religion; Buddhistin; Weibliche Hindu; Handlungskompetenz; Frau; Buddhismus; Hinduismus